Implementasi Sistem Smart Parking Menggunakan Raspberry Pi Pico W Berbasis Internet Of Things - Sholika Khairinnisa Siregar; Ahmad Dani; Beni Satria (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to design and implement an Internet of Things (IoT)-based Smart Parking system using a Raspberry Pi Pico W as the main controller and the Telegram Bot API as the user interface. The system is developed to monitor parking space availability in real time and to operate an automatic gate using a servo motor. The research methodology includes hardware design, microcontroller programming in Python, and integration with Telegram Bot for remote notifications and control. Experimental results show that the system can accurately detect parking status changes with 100% accuracy and respond in less than two seconds. The use of Telegram Bot enables efficient and lightweight remote access without the need for additional applications or complex servers. This study demonstrates that the integration of IoT and cloud messaging services provides an effective solution for intelligent parking systems that enhance efficiency, automation, and support the development of smart city concepts.